Association analysis of-429T/C and-374T/A polymorphisms of receptor of advanced glycation end products (RAGE) gene in Malaysian with type 2 diabetic retinopathy - Ng, Z.X.; Kuppusamy, U.R.; Tajunisah, I.; Fong, K.C.S.; Chua, K.H. (2012)
Conflicting results have been reported in different populations on the association between two particular RAGE gene polymorphisms (-429T/C and -374T/A) and retinopathy in diabetic patients. Therefore this study was designed to assess the association between both gene polymorphisms with retinopathy in Malaysian diabetic patients. A total of 342 type 2 diabetic patients 171 without retinopathy (DNR) and 171 with retinopathy (DR) and 235 healthy controls were included in this study. Genomic DNA was obtained from blood samples and the screening for the gene polymorphisms was done using polymerase chain reaction-restriction fragment length polymorphism approach. Overall, the genotype distribution for both polymorphisms was not statistically different (p > 0.05) among the control, DNR and DR groups. The -429C minor allele frequency of DR group (12.0%) was not significantly different (p > 0.05) when compared to DNR group (16.1%) and healthy controls (11.3%). The -374A allele frequency also did not differ significantly between the control and DNR (p > 0.05), control and DR (p > 0.05) as well as DNR and DR groups (p > 0.05). This is the first study report on RAGE gene polymorphism in Malaysian DR patients. In conclusion, -429T/C and -374T/A polymorphisms in the promoter region of RAGE gene were not associated with Malaysian type 2 DR patients. (C) 2011 Elsevier Ireland Ltd. All rights reserved.